Exchanging Medical Records: The Hypermedata Solution - Maurice Dixon; Jana Kohoutkova; Stephen Cook; Keith Jeffery; Brian Read (Journal of Innovation in Health Informatics, 1998)
There is increasing demand for the exchange of medical records between hospitals and general practices1. The provision of such an exchange encounters formidable obstacles in terms of the format and the content of the exchanged records2. We describe an architecture and a representation for the exchange of medical records between different medical centres as used in Hypermedata3, a research and development project. It includes both simple data types and complex structures, thus allowing us to describe text, graphs, tables, photographs, scans, and digitised data. We describe how a reference model is used with a domain ontology in order to allow consistent semantics to be achieved4,5. Inherent in the design of Hypermedata's architecture is the certainty that local medical systems will always evolve in time, so Hypermedata detects when it is necessary to reconstruct the exchange schema for a new exchange2. The problems faced by Hypermedata are of a general nature for inter-operating systems and the proposed solutions are applicable to other systems.